2018
DOI: 10.1115/1.4040940
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamic Study for aTAA Hemodynamics: An Integrated Image-Based and Radial Basis Functions Mesh Morphing Approach

Abstract: We present a novel framework for the fluid dynamics analysis of healthy subjects and patients affected by ascending thoracic aorta aneurysm (aTAA). Our aim is to obtain indications about the effect of a bulge on the hemodynamic environment at different enlargements. 3D surface models defined from healthy subjects and patients with aTAA, selected for surgical repair, were generated. A representative shape model for both healthy and pathological groups has been identified. A morphing technique based on radial ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 51 publications
2
39
0
Order By: Relevance
“…This effort arises from a twofold need: from one side, to stratify the risk of LAA thrombus formation in AF patients, and, on the other hand, to develop new percutaneous closure procedures. Previous studies have demonstrated the alterations in shape, size and contraction patterns of LAA in AF condition by using different imaging techniques [12,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…This effort arises from a twofold need: from one side, to stratify the risk of LAA thrombus formation in AF patients, and, on the other hand, to develop new percutaneous closure procedures. Previous studies have demonstrated the alterations in shape, size and contraction patterns of LAA in AF condition by using different imaging techniques [12,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergo elective repair of the ATAA on the basis of the size and progression rate of the aortic diameter, but aortic size has a limited predictive value, as adverse events may occur when aortic diameters are <55 mm, and even <45 mm [10]. Among novel approaches for risk stratification, computational modeling has shown promise in the estimation of ATAA by means of prediction of intramural stress [11] and shear stress [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…CFD simulation helps to overcome this limitation and was able to predict the WSS and other biomechanical parameters more accurately using the physiological blood flow condition obtained from 4D MRI data. The need for evaluating the impact of ATAAs on biomechanical properties and blood flow was emphasized in a number of previous studies . To address this need, the current article proposed a thorough and robust computational framework combining 4D MRI and CFD to study the influence of changes in aortic morphology on a number of biomechanical descriptors.…”
Section: Discussionmentioning
confidence: 99%